El momento maquiaveliano y la teoría política: una propuesta de articulación - Morán, Sabrina; Rodríguez Rial, Gabriela (Conceptos Históricos, 2020)
The publication of J. G. A. Pocock’s The Machiavellian Moment: Florentine Political Thought and the Atlantic Tradition in 1975 is framed in the rehabilitation of republican thought that, during the past decades, has had an impact on History (of ideas and processes) and Political Philosophy. This revival was inaugurated by the English-speaking and French academy, and then expanded to other places. The aim of this article is to analyze the senses of the “Machiavellian moment” since its formulation by Pocock, breaking down its meanings, exemplifying its uses and reconsidering some of the main critiques it has received. Although History and Political Philosophy have critically accepted the legacy of the neo-republican debate and have identified the potentialities and weaknesses of the “Machiavellian moment” as an analytical category, Political Theory has remained on the sidelines of this debate. Here lies the relevance of our asking to what extent the “Machiavellian moment” is indeed a heuristic tool that contributes to the understanding of the political and of politics both in their repetition and contingency.